Bridging the Skills Gap Curriculum Transformation for Automation Industries and the Role of Digital Technopreneurship - Tjahjono, Budi; Hermawan, Dadang; Millah, Shofiyul; Evans, Richard (Pandawan, 2025)
The rapid advancement of digital technology and industrial automation has compelled vocational education to undergo significant curriculum transformation to produce graduates equipped for the demands of the modern workforce. A persistent gap between educational content and industry requirements poses a critical challenge that must be addressed strategically. This study aims to examine the transformation of vocational curricula in preparing students with essential digital and automation related competencies, with a specific focus on the role of digital technopreneurship. The research employs a mixed-method approach, including literature reviews, curriculum analysis, and semi structured interviews with stakeholders from vocational institutions and automation driven industries. The findings highlight the urgent need to integrate emerging technologies such as automation systems, Artificial Intelligence (AI), the Internet of Things (IoT), and data analytics into vocational programs to enhance their alignment with industrial needs. Additionally, the development of cross functional skills, including communication, teamwork, critical thinking, and problem solving, is identified as crucial to graduates success in dynamic work environments. The study underscores the importance of collaborative partnerships between educational institutions and industry players in designing adaptive, future ready curriculum. Furthermore, sustained investment in educational infrastructure and continuous professional development for educators is essential to ensure effective delivery of technology oriented learning. Future research is recommended to explore scalable models of curriculum innovation and to evaluate the long term impacts of digital skill integration on workforce competitiveness in the Industry 4.0 era.